The Relationship between Body Perception and Nutrition of B2 - B3 Impaired Athletes - Dalbudak, Ibrahim; Balyan, Melih; Zekioglu, Aylin; Basoglu, Umut Davut; Manci, Egemen (Progress in Nutrition, 2021)
Study Objectives: It is aimed to investigate the relationship between body perception and nutrition of b2-b3 visually impaired athletes. In addition, another aim of this study is to determine the knowledge of b2-b3 visually impaired athletes about body perception and nutrition. Methods: The study was conducted with the participation of a total of 108 volunteers, 40 women and 68 men, from b2-b3 visually impaired athletes, who played professionally in different clubs, and the relationship between body perception and nutritional variables and demographic characteristics were analyzed. Volunteering was taken into account in participation. As the data collection tool, the "Personal Information Form" and the body perception scale developed by Secord and Jourard, whose validity and reliability study was conducted and adapted into Turkish by Hovardaoğlu, and the three-factor nutrition scale developed by Karlsson et al. were used. Results: Body perception scale total score means of the individuals differ significantly according to gender and educational status (p<0.05). No significant differences were obtained for other demographic variables (p>0.05). While there was a significant difference in the four-factor nutrition questionnaire of the individuals and the subscales according to gender (p<0.05), there was no significant difference in terms of age and disability status, sports branch, education status, income status, vision level (p>0.05). There was a statistically significant strong positive directional relationship between Body Perception Scale and Four Factor Nutrition Survey (p<0.05). Conclusion: It was determined that the training programs, competitions, and resting intervals of the sports life of B2-B3 visually impaired athletes have an effective role on body perception as they have a controllable nutritional habit. In short, we can say that the thoughts or ideas of visually disabled athletes about body perception are extremely effective on nutrition.